Problems of secondary school students outstanding schools in the city of lattakia - نزيهة ريما; أميرة زمرد; سمر يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the current research is to identify the problems facing secondary school students in the city of Lattakia. The differences in these problems were identified according to the two variable: gender, grade. The researcher used the descriptive method. The achieve the objective of the research. A questionnaire consisting, divided into three axes ( The focus of students problems related to school administration, The focus of students problems related to the teacher, and the focus of students problems stemming from them( educational, psychological, and social problems)). The questionnaire was applied to a sample of(107) male and female students from the school of excellence in the city of lattakia for the academic year 2021\2022. The results of the research showed that the outstanding students suffer from problems related to school administration and the teacher to a medium degree. While they don’t suffer from problems stemming from them (educational, psychological, social problems). As for the problem faced by the students on the questionnaire as a whole, they came to a medium degree. It was also found that there s no difference in the problems between students with regard to the gender of the student, whether male or female, as well as for his grade, whether the first secondary. Second secondary or third secondary. Based on what has been researcher suggests the necessity of conducting studies on the investigation of the problems faced by outstanding students in the absence of local studies on their investigation. And go to the various parties related to the research( students, teachers, and managers) and the need to tighten control over the teaching process in school of outstanding students. And work to improve the school of outstanding students and take care of them scientifically and psychologically.